Shaping the Future of Respiratory Care: A look into the next decade and strategic recommendations by EUFOREA. - Bertels,X; Scadding,G; Backer,V; Lau,S; Wj,F; Barnes,P; Sprekelsen,MB; Bjermer,L; Blaiss,M; Borzova,E; Brüggen,M; Brusselle,G; et al. (Chest, 2026)
Chronic respiratory diseases (CRDs) remain one of the leading causes of preventable morbidity and disability worldwide, and affect up to one-third of the total Western population in 2025. Recognising the substantial burden of inflammatory airway diseases such as asthma, chronic obstructive pulmonary disease (COPD), chronic rhinosinusitis (CRS) and respiratory allergy, the European Forum for Research and Education in Allergy and Airway Diseases (EUFOREA) organised the symposium "Shaping the Future of Respiratory Care" in April 2025 in Brussels, Belgium at the occasion of the 10 year jubilee. Featuring keynote speakers from the World Health Organization (WHO) and EUFOREA, this initiative had the following aims: (i) promoting dialogue on translating innovations into daily clinical practice, (ii) encouraging collaboration between the different stakeholders in the respiratory field, and (iii) defining strategic priorities to transform respiratory care and arrest the CRD epidemic over the next decade. The symposium highlighted the importance of moving towards predictive, preventive, and patient-centred medicine, while supporting value-based healthcare systems to improve long-term patient outcomes. This report summarises the main insights and strategic directions discussed at the meeting.